Bridging Language and Learning: A Genre-Based Writing Assessment Model for Indonesian Bilingual Classrooms - Oktora, Maya; ., Sumarsih; ., Meisuri (Journal of Posthumanism, 2025)
This research developed and implemented a genre-based writing assessment model incorporating self-assessment guided by metacognitive principles to improve students’ academic writing. Employing a qualitative design, the study involved classroom-based implementation and analysis of student writing performance, lecturer feedback practices, and student reflections. Data were collected through writing samples, rubric-based evaluations, and participant interviews. The findings reveal that the integration of a structured self-assessment model fosters shared understanding between lecturers and students about the expectations of genre-specific writing. Lecturers’ enhanced linguistic knowledge was essential in ensuring the reliability of assessment and in delivering more targeted instruction. The findings underscore the importance of aligning assessment practices with pedagogical goals and integrating digital tools to support active, student-centered learning. This model holds practical implications for Indonesian universities aiming to improve academic writing instruction and better prepare students for participation in global academic discourse.